PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN CITRA BANK TERHADAP KEPUASAN NASABAH ERA COVID 19 (STUDI KASUS DI PT. BANK MANDIRI KANTOR CABANG PALEMBANG) - Rora Rosmaya Sari; Luis Marnisah; Fakhry Zamzam (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
This study aims to analyze the effect of service quality, product quality and bank image on customer satisfaction. The population in this study were customers at PT. Bank Mandiri Palembang Branch Offices totaling 174,363 people. Determination of the sample using the Slovin formula, in order to obtain a sample of 100 people with incidental sampling technique. The analysis technique uses multiple linear regression with hypothesis testing using the t test and the F test. The results show that partially the variables of service quality and bank image have a significant and significant effect on customer satisfaction at Bank Mandiri. Meanwhile, the variable of product quality has an effect and is not significant towards the customer satisfaction of Bank Mandiri. Together, the variable service quality, product quality, and image of the bank simultaneously have an effect and are significant on customer satisfaction at Bank Mandiri. It is hoped that Bank Mandiri will further improve service quality, such as maintaining the banking system so that it always runs well, providing good and appropriate solutions, and maintaining a high corporate image as a customer image.